Tracked Changes. Electromagnetic compatibility (EMC). Limits. Limitation of voltage changes, voltage fluctuations and flicker in public low-voltage supply systems, for equipment with rated current <= 16 A per phase and not subject to conditional connection Part 3-3, (19th November 2019) - British Standards Institution,
No abstract available